ChemInform Abstract: Palladium‐Catalyzed Direct Thiolation of Aryl C—H Bonds with Disulfides. Issue 35 (2nd September 2014) - Iwasaki, Masayuki; Iyanaga, Miki; Tsuchiya, Yuta; Nishimura, Yugo; Li, Wenjuan; Li, Zhiping; Nishihara, Yasushi
Abstract The title reaction proceeds with ortho‐selectivity induced by a directing group.